Properties of Oil Palm frond and Kenaf Bast Bio-composites Boards. - Razak Wahab; Hashim W. Samsi; Mohd Tamizi Mustafa; Madihan Yusof; Othman Sulaiman; Izyan Khalid; Mohd Sukhairi Mat Rasat (RJPBCS, 2015)
Properties of bio-composite boards made from mixture of fibers from oil palm fronds (OPF), and kenaf bast fibers (KBF) at five different ratios were investigated. Urea formaldehyde resin at 10%, 12%, and 14% was used in bonding the mixtures together. The micrographs' structures obtained through scanning electron microscopy were used in determining the distribution of the resin in the boards. The EFB and kenaf bast fibers were mixed at ratios of 100:0, 70:30, 50:50, 30:70, 0:100 (OPF: KBF). All testing, specimen size and shape were done in accordance with the European EN Standards. Testing on the physical properties included moisture content, water absorption and thickness swelling, density and contact angle and mechanical testing included static bending for MOE, MOR, and internal bonding of the boards revealed the enhanced values after increasing the resin content. The overall results showed that boards of 100% OPF with 14% of resin content exhibited the highest properties compared to the other boards. It was found that mixture of different fibers can be good combination for fabrication of new candidates.